RESEARCH OF THE PRIMARY PROCESSING OF OSTRICH SKIN FOR EXOTIC LEATHER (Scientific journal of the Fergana State University, 2023)
The article provides information on the rapid growth of the ostrich farming industry in Uzbekistan, on the profitability of the ostrich skin in producing the exotic leather in comparison with other products. The features on removal, conservation, storage and varieties of ostrich skins, as well as data on the use of exotic ostrich skin for the manufacture of various leather products have been shown.